Coronary atherosclerosis on AI-based plaque analysis in patients with chest pain and calcium score zero - Molnar, David; Knuuti, Juhani; Bax, Jeroen J.; Saraste, Antti; Maaniitty, Teemu (Springer Nature, 2026)
There is conflicting evidence on the prevalence of obstructive and non-obstructive coronary artery disease (CAD) and outcome in symptomatic patients with zero coronary artery calcium score (CACS). To characterize sex differences in coronary atherosclerosis in patients with chest pain and zero CACS. Patients evaluated for suspected CAD at Turku University Hospital 2006–2016 with zero CACS were included. In addition to clinical reading, artificial intelligence-based quantitative analysis (AI-QCT) of coronary computed tomography angiography (CTA) images was performed. Long-term clinical outcome of myocardial infarction, unstable angina or death was analyzed. Out of 2,216 patients with CTA results, 606 had zero CACS (156 men and 450 women, median age 54 vs. 61). Around 5% of men and 2% of women with zero CACS had obstructive CAD, with comparable findings on clinical CTA and AI-QCT. Non-obstructive disease was found in higher proportion on AI-QCT (88.5% of men and 85.6% of women) than on clinical reading (16.7% of men and 11.6% of women). Non-calcified plaques dominated, but small calcifications were not uncommon. Low-density plaques increased with the severity of CAD. After a median follow-up of 7.3 years, only 3 men and 14 women experienced clinical events, yielding an annual event rate of 0.26% in men and 0.43% in women. In patients with suspected CAD and zero CACS obstructive CAD is detected in around 5% of men and 2% of women. Non-obstructive CAD is detected in a vast majority with AI-QCT. Despite this, long-term clinical outcome is generally very good.